Beyond informed consent: the therapeutic misconception and trust. Issue 3 (3rd March 2008) - de Melo-Martín, I; Ho, A
Abstract : The therapeutic misconception has been seen as presenting an ethical problem because failure to distinguish the aims of research participation from those receiving ordinary treatment may seriously undermine the informed consent of research subjects. Hence, most theoretical and empirical work on the problems of the therapeutic misconception has been directed to evaluate whether, and to what degree, this confusion invalidates the consent of subjects. We argue here that this focus on the understanding component of informed consent, while important, might be too narrow to capture the ethical complexity of the therapeutic misconception. We show that concerns about misplaced trust and exploitation of such trust are also relevant, and ought to be taken into account, when considering why the therapeutic misconception matters ethically.